2012
DOI: 10.1172/jci62973
|View full text |Cite
|
Sign up to set email alerts
|

ER stress–mediated autophagy promotes Myc-dependent transformation and tumor growth

Abstract: The proto-oncogene c-Myc paradoxically activates both proliferation and apoptosis. In the pathogenic state, c-Myc-induced apoptosis is bypassed via a critical, yet poorly understood escape mechanism that promotes cel-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
304
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 348 publications
(325 citation statements)
references
References 69 publications
10
304
0
2
Order By: Relevance
“…Previously, several studies have shown PBA, a well-known chemical chaperone, inhibited ER stress-mediated apoptosis. 40,41 In accordance with these reports, we showed that PBA alleviates ER stress response induced by aldosterone in podocytes. Treatment with PBA downregulated UPR-related proteins including Bip, grp94, and Chop.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, several studies have shown PBA, a well-known chemical chaperone, inhibited ER stress-mediated apoptosis. 40,41 In accordance with these reports, we showed that PBA alleviates ER stress response induced by aldosterone in podocytes. Treatment with PBA downregulated UPR-related proteins including Bip, grp94, and Chop.…”
Section: Discussionsupporting
confidence: 91%
“…Instead, signaling due to increased ER stress drives autophagy independent of the mTOR pathway in these cells. The unfolded protein response has previously been linked to induction of autophagy in disease contexts like cancer and neurodegenerative diseases (43,44). Signaling through both the PERK-and IRE-dependent arms of the unfolded protein response has been linked with induction of autophagy (for review see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, ER stress has proved to be one of the inducers of autophagy. 22 Interestingly, DHA induced-ER stress has been observed in several tumor cells, 23,24 and our previous studies have demonstrated that DHA both induce apoptosis and autophagy in various cancer cells. 25,26 The Complex relationships among ER stress, autophagy and apoptosis remain unclear, but it's perhaps noteworthy that we found p8 is involved in all of these 3 biological functions induced by DHA.…”
Section: Introductionmentioning
confidence: 93%